The Effect of Motivation and Competence on Employee Performance: A Study at the Social Service of South Sulawesi Province - Andi Hendra Syam (Manunggal Halim Jaya, 2022)
This study aims to determine and analyze the influence of motivation and competence on employee performance at the Social Service Office of South Sulawesi Province. This research was carried out using a quantitative descriptive approach to obtain a complete picture of the variables studied. This type of research is a survey, namely analyzing the data needed to support the research discussion in solving and answering the problems that have been formulated. Multiple linear regression is the analysis of the data used in this study. Based on the results of the analysis of this study, it proves that motivation has a positive and insignificant effect on employee performance as evidenced by the significance (probability) = 0.985, which shows above from probability (sig) = 0.000 < = 0.05 and the contribution value of B1 = 0.001 or 0, 01%, while the effect of competence on employee performance in the Social Service of South Sulawesi Province shows a positive and significant effect on employee performance as evidenced by the significance (probability) = 0.000 below = 0.05. The competency variable (X2) has the two independent variables' most significant and dominant coefficient.